2020
DOI: 10.1002/lary.29072
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pass/Fail USMLE Step 1 Scoring on the Otolaryngology Residency Application Process

Abstract: Objectives To investigate how the decision to report United States Medical Licensing Examination (USMLE) Step 1 score as pass/fail will influence future otolaryngology residency application and match processes. Study Design Survey study. Methods An anonymous and voluntary survey approved by the Otolaryngology Program Directors Organization was administered to academic faculty members from April 24, 2020 through May 19, 2020. Results Two hundred fifty‐seven surveys were received from department chairs (17.5%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 25 publications
4
64
0
Order By: Relevance
“…Our findings are similar to a recent survey of otolaryngology program directors, which showed that recent changes in USMLE exams are anticipated to increase the significance of core clerkship grades and elective rotations at respective institutions, Alpha Omega Alpha and other awards, and [16]. They also anticipate that this change will negatively impact international medical graduates, Osteopathic Medicine Doctors, and underrepresented students [16]. We found that 42% of surgery programs are moving from a traditional approach to a holistic approach for their upcoming residency selection process.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are similar to a recent survey of otolaryngology program directors, which showed that recent changes in USMLE exams are anticipated to increase the significance of core clerkship grades and elective rotations at respective institutions, Alpha Omega Alpha and other awards, and [16]. They also anticipate that this change will negatively impact international medical graduates, Osteopathic Medicine Doctors, and underrepresented students [16]. We found that 42% of surgery programs are moving from a traditional approach to a holistic approach for their upcoming residency selection process.…”
Section: Discussionsupporting
confidence: 90%
“…The schools that will be best prepared to handle the increased emphasis on Step 2 CK are many of the top medical schools that require students to take Step 1 and Step 2 CK after completing their core clinical rotations during their third year, rather than at the beginning of their second year. Our findings are similar to a recent survey of otolaryngology program directors, which showed that recent changes in USMLE exams are anticipated to increase the significance of core clerkship grades and elective rotations at respective institutions, Alpha Omega Alpha and other awards, and letters of recommendation [ 16 ]. They also anticipate that this change will negatively impact international medical graduates, Osteopathic Medicine Doctors, and underrepresented students [ 16 ].…”
Section: Discussionsupporting
confidence: 89%
“…The aim of this study was to compare the perceptions among program directors (PDs) in orthopaedics and IM on the change of Step 1 from a graded to a pass/fail exam, and its impact on the residency application process. Some groups have studied PD opinions of the Step 1 pass/fail change; however, to the best of our knowledge, the current study is the first comprehensive survey to directly compare the impact on medicine and a surgical subspecialty [4][5][6][7][8][9][10][11][12]. We chose to study IM PDs because IM has historically been a popular specialty that has had the most number of total applicants.…”
Section: Introductionmentioning
confidence: 99%
“…These findings underscore the importance of well‐known variables for otolaryngology applicant success such as board scores, research, and clerkship grades 8‐11 . They also provide novel insight into the importance of personal and geographic connections between applicants and programs.…”
Section: Discussionmentioning
confidence: 64%
“…This study has several limitations. The Texas STAR database did not contain information about letters of recommendation, which are considered by faculty to be one of the most important factors for otolaryngology match success 8 . Additionally, it did not contain information on medical school NIH‐funding which has previously been shown to correlate with otolaryngology match success 10 .…”
Section: Discussionmentioning
confidence: 99%